2020
DOI: 10.1021/acs.energyfuels.0c00965
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on CO2 Foam Films with Sodium Dodecyl Sulfate: Effects of Surfactant Concentration, Temperature, and Pressure on the Interfacial Tension

Abstract: CO2 foam flooding technology can be used for geological storage of greenhouse gas CO2 while enhancing oil recovery. In this paper, we performed molecular dynamics simulations for the CO2 foam film systems stabilized with an anionic surfactant of sodium dodecyl sulfate (SDS). Compared to other factors of a foam system, interfacial tension was used as the primary indicator to evaluate the stability of the SDS foam film. The effects of the concentration of the SDS surfactant, temperature, and pressure on the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…26,27,29,39,44,45 It is also known that the addition of surfactants such as sodium dodecyl sulfate (SDS) generally decreases the IFT. [46][47][48][49][50][51][52][53][54][55][56][57][58] Molecular simulations showed that, in the water + surfactant system, water molecules and sodium counterions are relatively near the SDS headgroups. 49,[51][52][53][54][55][56][57][58] Bruce et al found distortions in the water-water hydrogen bonding network because of the SDS-water hydrogen bond formations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27,29,39,44,45 It is also known that the addition of surfactants such as sodium dodecyl sulfate (SDS) generally decreases the IFT. [46][47][48][49][50][51][52][53][54][55][56][57][58] Molecular simulations showed that, in the water + surfactant system, water molecules and sodium counterions are relatively near the SDS headgroups. 49,[51][52][53][54][55][56][57][58] Bruce et al found distortions in the water-water hydrogen bonding network because of the SDS-water hydrogen bond formations.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55][56][57][58] Molecular simulations showed that, in the water + surfactant system, water molecules and sodium counterions are relatively near the SDS headgroups. 49,[51][52][53][54][55][56][57][58] Bruce et al found distortions in the water-water hydrogen bonding network because of the SDS-water hydrogen bond formations. 49 Lin et al found that, in the water + surfactant + CH 4 system, the solubility of CH 4 in water is not affected by the presence of SDS molecules at the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of amphiphilic molecules, also known as surfactants, to tune the surface tension of fluids is essential for stabilizing foams of CO 2 bubbles dispersed in water at elevated temperature and pressure, which enables effective utilization of pore space for geologic storage of CO 2 . Furthermore, surfactant chemistries can be tuned for developing pharmaceutical therapies to enhance lung capacity and respiration, delivering medicines that have low solubility in water, , advanced separations for water purification, and the synthesis of novel materials with tunable porous architectures for catalysis, gas separations, and storage. These wide-ranging applications are attributed to the structures of surfactants, which are formed due to the aggregation or assembly of their molecules. A surfactant molecule has a bulk hydrophilic head, which is sometimes charged, and a relatively short hydrophobic tail .…”
Section: Introductionmentioning
confidence: 99%
“…In this process, CTAB is preferentially adsorbed on the rock surfaces, , resulting in a reduction of interfacial tension between the oil and rock. With increasing interest in harnessing CO 2 as a working fluid in subsurface environments (e.g., CO 2 foams ), a fundamental understanding of the assembly of surfactants at solid interfaces is crucial to inform advances in the use of CO 2 or alternative fluids that require the use of CTAB for subsurface energy applications.…”
Section: Introductionmentioning
confidence: 99%